Tasa relativa de crecimiento en plántulas de dos poblaciones de Magnolia pugana (Magnoliaceae) en distintos niveles de luz y fertilidad del suelo - García Castro, Karla Denisse (2018)
Relative growth rate in Magnolia pugana (Magnoliaceae) seedlings from two populations at different light levels and soil fertility. The study of ecophysiology of endangered species is key to the success of conservation and ecological restoration programs. The objective of this work was to know the effect of light, soil fertility and seed origin on the growth of Magnolia pugana seedlings. The relative growth rate (RGR) and its components (Net Assimilation Rate: NAR and Leaf Area Ratio: LAR), as well as the root-shoot ratio (R/S) were estimated. Seedlings were obtained from seeds collected in two localities in Zapopan, Jalisco, Mexico, the first is a wild population in San Nicolás (SN) and the second is a plantation located in the gardens of the Centro Universitario de Ciencias Biológicas y Agropecuarias (CUCBA). The experiment was conducted under greenhouse conditions. In September 2015, 96 seedlings of approximately three months old were subjected to the following treatments in a factorial experiment (2x2x2): light level (high = 1 120 μmol m-2 s-1 and low = 136.3 μmol m-2 s-1), seedling origin (SN and CUCBA) and soil fertility (high fertility = SN soil, low fertility = CUCBA soil) with 12 replicates for each combination of factors and levels. Growth was estimated in two harvests: the first harvest after 30 days of starting the experiment and the second at 60 days. Light and soil fertility levels, as well as seedling origin influenced growth through physiological and morphological adjustments. In general, Magnolia pugana showed higher RGR and NAR in high light, while LAR decreased. Soil fertility and seedling origin did not affect RGR or its components. However, these were affected by the light level, seedlings from SN grew more in high light. Stem height varied due to soil fertility and seedling origin, in low fertility soil (CUCBA) the seedlings of SN were 35 % higher than those of CUCBA. Low fertility soil under high light caused greater investment in seedling root biomass. The physiological component (NAR) was the major determinant of intraspecific variation in RGR. SN seedlings showed greater phenotypic plasticity due to coming from a wild population, which possibly has higher genetic variation than the cultivated population from CUCBA. The results suggest that Magnolia pugana is a species capable of adapting to diverse environments due to its phenotypic plasticity in response to different light and soil fertility levels. Rev. Biol. Trop. 66(2): 622-633. Epub 2018 June 01.